THE BENEFITS OF READING ALOUD IN EFL CLASSES: USING LITERATURE TO IMPROVE PRONUNCIATION AND FLUENCY - Fayzullayeva Diyora (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Reading aloud in English as a Foreign Language (EFL) classrooms offers a dynamic approach to bridging linguistic theory with real-world application. This study delves into the transformative impact of incorporating literature-based oral reading exercises to improve pronunciation, fluency, and overall speaking confidence. By engaging with authentic literary texts, learners are exposed to rich language patterns, varied intonations, and meaningful contexts, allowing them to internalize the rhythm and flow of English naturally. The findings highlight that literature fosters an emotionally engaging and motivational environment, encouraging learners to connect deeply with the language while building linguistic and cultural awareness. Challenges such as mastering pronunciation and maintaining rhythm were acknowledged, emphasizing the importance of teacher-guided support. Despite these obstacles, the benefits of reading aloud—such as increased confidence, improved fluency, and expanded vocabulary—strongly affirm its value as a creative and effective pedagogical tool. This study shows the importance of integrating literature into EFL classrooms to create a comprehensive and enriching language learning experience.